Surfacing values through rubric development. Why and how. - King, Julian (Evaluation and Value for Investment, 2024)
This article provides a comprehensive overview of rubric development in evaluation practice, focusing on stakeholder engagement and practical implementation. King explains that rubrics are essential tools for implementing evaluative reasoning, serving as frameworks that combine evidence, criteria, and standards to make transparent value judgments. The piece emphasizes that effective rubric development is inherently participatory, requiring meaningful stakeholder engagement for both ethical and practical reasons. The author presents detailed guidance for practitioners, including tips for facilitating stakeholder involvement, creating safe collaborative spaces, and maintaining simplicity while ensuring context-specificity. Through various real-world examples, King illustrates the flexible nature of rubric development processes, from two-hour workshops to multi-year evaluations. The article argues that while rubric development requires significant upfront investment, it pays dividends throughout the evaluation process by enhancing clarity, stakeholder buy-in, and ultimate utility of evaluation findings. Written as pre-workshop reading for training sessions in London, the piece serves both as an introduction for newcomers and a detailed reference for experienced evaluators.

Sense-making with stakeholders and rubrics - King, Julian (Evaluation and Value for Investment, 2023)
Principles and processes

Different kinds of rubrics - King, Julian (Evaluation and Value for Money, 2023)
Generic, analytic, holistic, orbic, asterisc, escalieric, cephalopodic

Evaluative reasoning in complexity - King, Julian (Evaluation and Value for Investment, 2023)